Foundations of F# - Pickering, Robert (Apress : Imprint: Apress, 2007)
Functional programming (FP) is the future of .NET programming, and F# is much more than just an FP language. Every professional .NET programmer needs to learn about FP, and there's no better way to do it than by learning F#, and no easier way to learn F# than from Foundations of F#. If you're already familiar with FP, youll find F# the language youve always dreamed of. All .NET programmers will find F# an exciting real-world alternative to C# and Visual Basic. This book is likely to have many imitators, but few true competitors. Written by F# evangelist Rob Pickering, and tech reviewed by F#'s main designer, Don Syme, this is an elegant, comprehensive introduction to all aspects of the language and an incisive guide to using F# for real-world professional development. F# is the future of programming (not just on .NET), and the future is now.